Exercise intervention in the management of urinary incontinence in older women in villages in Bangladesh: a cluster randomised trial. Issue 7 (July 2019) - Wagg, Adrian; Chowdhury, Zafrullah; Galarneau, Jean-Michel; Haque, Rezaul; Kabir, Fardous; MacDonald, Dianna; Naher, Kamrun; Yasui, Yutaka; Cherry, Nicola
Summary: Background: Group exercise-based programmes for urinary incontinence appear to be promising low-cost interventions for women in developing countries, but no evidence exists to support whether they could be implemented or effective in such populations. We aimed to evaluate whether a group intervention that comprised pelvic floor muscle training, mobility exercises, and bladder education would be more effective than education alone, and report changes between villages (ie, clusters) rather than between individual participants. Methods: In this cluster randomised trial, we recruited women from 16 pairs of villages in Bangladesh, with each pair comprising similar villages from the same sub-district. Women aged 60–75 years were interviewed to establish eligibility. Women were eligible if they had current urinary incontinence, and were excluded if they had a third degree or higher uterine prolapse, if they were unable to walk or stand without help, or if they had insufficient intellectual capacity to understand questions and follow instructions. The villages were randomly assigned within each pair to either exercise plus education or education-only intervention by use of a random number generator from a fixed seed. Women were excluded after consenting if they lived too far from the centre of the village. The exercise intervention was a physiotherapist-led group exercise class that was held twice weekly for 12 weeks, with home exercises between classes and to 24 weeks. Both groups received bladder-health education. Participants were followed up for 24 weeks. A 3-day continence record was collected at recruitment and every 4 weeks up until 24 weeks. This record involved the participant tying a knot in ribbons worn under the clothing each time they had an episode of urinary leakage. The primary outcome was change in number of knots (recorded leakage episodes) from recruitment to 24 weeks. Safety was assessed in all participants in the exercise intervention group. The trial is registered at ClinicalTrials.gov, number NCT02453100 . Findings: Between Aug 22, 2015, and July 2, 2018, of 3577 women aged 60–75 years identified, 1003 were eligible, of whom 625 consented to participate (n=335 exercise plus education villages, and n=290 in education-only villages). Of these consenting women, 46 were excluded (n=37 exercise plus education, n=9 education only) because they lived too far from the centre of the village. At week 24, 283 (95%) of 298 in the exercise plus education group and 274 (98%) of 281 in the education-only group completed a 3-day continence record. The estimate of change in number of leakage episodes between baseline and 24 weeks was −7·7 (95% CI −10·6 to −4·8) at the village level in an unadjusted model, and −6·64 (–7·95 to −5·33) in a random-effects model accounting for cluster randomisation. No adverse events were reported. Interpretation: A structured group-exercise intervention has the potential to manage urinary incontinence in older women in communities largely outside the reach of pharmaceutical or surgical interventions. Funding: Canadian Institutes for Health Research.